Two approaches in the treatment of malignant obstructive jaundice using nitinol stents - R. M. Nagaev; I. V. Yangirov; D. Y. Frantsev; G. A. Starkov; G. A. Gasanbekov; A. V. Laskevich (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The article presents our experience of observing two different approaches for endoscopic retrograde drainage in patients with malignant pathology of the pancreatobiliary zone, complicated by the bile duct obstruction. In one case, in case of dysfunction of the installed uncovered stent as a result of incrustation with bile salts and/or tumor invasion, stent-to-stent restenting was performed. In the second case, if it was impossible to pass the guidewire retrogradely beyond the area of the tumor narrowing, an alternative method was used – bringing it down by percutaneous transhepatic access towards the endoscope to install a retrograde stent delivery system along it using the "Rendezvous" method.